2020
DOI: 10.1111/iej.13405
|View full text |Cite
|
Sign up to set email alerts
|

Root canal treatment of compromised teeth as alternative treatment for patients receiving bisphosphonates: 60‐month results of a prospective clinical study

Abstract: AimThis 60‐month prospective study aimed to evaluate tooth survival and healing rates after root canal treatment in patients taking bisphosphonates (BPs). Secondary outcomes were complications and clinical variables observed during and after treatment.MethodsRoot canal treatment was performed using manual K‐file canal instrumentation and a carrier‐based filling technique with an epoxy resin‐based sealer. Teeth without adequate root/crown integrity were restored by trained operators at the tissue level (TL grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…An apparently healthy patient may potentially create the condition for a sequence of serious contaminations. For these reasons, HDWs i.e., dentists, dental staff personnel, students and patients must be protected (Figure 2D,E), in particular whose affected by systemic diseases [31].…”
Section: Discussionmentioning
confidence: 99%
“…An apparently healthy patient may potentially create the condition for a sequence of serious contaminations. For these reasons, HDWs i.e., dentists, dental staff personnel, students and patients must be protected (Figure 2D,E), in particular whose affected by systemic diseases [31].…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of calcified root canals, 3.0 mL of 10% EDTA solutions was used as a calcium chelating agent. A final irrigation of 2.0 mL sterile water was made before root canal filling procedures [ 26 , 27 , 28 ]. No intracanal medication was placed in accordance with previous studies [ 26 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of calcified root canals, 3.0 mL of 10% EDTA solutions was used as a chelating agent. A final irrigation of 2.0 mL sterile water was made before the root canal filling procedures [ 26 , 27 ]. When necessary, a dental surgery microscope (Pico, Zeiss, Germany) was used to detect the access to root canal orifices and to identify the presence of residual filling materials.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the results of this study, which created 5 different clinical scenarios requiring post core restoration after crown destruction, it is inevitable that there are clinical situations that require more conservative treatment needs where root canal treatment cannot be applied due to the use of various medications that may develop osteonecrosis. At this point, it has also been reported that tissue level filling procedures after root canal treatments and endodontic restoration are a safe approach in severely damaged teeth, especially in patients taking Bisphosphonates [ 58 ]. This is one of the limitations of this study.…”
Section: Discussionmentioning
confidence: 99%